Site-specific synergy in heterogeneous single atoms for efficient oxygen evolution - Peiyu Ma; Jiawei Xue; Ji Li; Heng Cao; Ruyang Wang; Ming Zuo; Zhirong Zhang; Jun Bao (Nature Communications)
Abstract Heterogeneous single-atom systems demonstrate potential to break performance limitations of single-atom catalysts through synergy interactions. The synergy in heterogeneous single atoms strongly dependes on their anchoring sites. Herein, we reveal the site-specific synergy in heterogeneous single atoms for oxygen evolution. The RuTIrV/CoOOH is fabricated by anchoring Ru single atoms onto three-fold facial center cubic hollow sites and Ir single atoms onto oxygen vacancy sites on CoOOH. Moreover, IrTRuV/CoOOH is also prepared by switching the anchoring sites of single atoms. Electrochemical measurements demonstrate the RuTIrV/CoOOH exhibits enhanced OER performance compared to IrTRuV/CoOOH. In-situ spectroscopic and mechanistic studies indicate that Ru single atoms at three-fold facial center cubic hollow sites serve as adsorption sites for key reaction intermediates, while Ir single atoms at oxygen vacancy sites stabilize the *OOH intermediates via hydrogen bonding interactions. This work discloses the correlation between the synergy in heterogeneous single atoms and their anchoring sites.